RISK FACTORS FOR STUNTING INCIDENTS IN CHILDREN TODDLERS IN TOROBULU VILLAGE OF LAEYA DISTRICT: STUNTING - Yuhadi, Asfani; Saparina L, Titi; Firmansyah, Firmansyah; Armayani, Armayani (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2024)
Background: One of the nutritional problems that has become a global focus is overcoming stunting in toddlers. Based on the 2023 Mandala Waluya University Student KKN Activity Report, information was obtained that many of the pregnant women in Torobulu village are teenagers, who do not have adequate knowledge, because many do not continue their basic education to high school. The aim of this research is to determine the risk factors for stunting among toddlers in Torobulu Village, Laeya District in 2024 Methods: The research used a case control study design. The sample consisted of 40 cases and 40 controls with gender. with matching gender the data analysis univariate. The sample technique uses simple random sampling. The data analysis used is odds ratio (OR) analysis. Results: The Research show that knowledge, exclusive breastfeeding, environmental sanitation and income are risk factors for the incidence of stunting in children under five in Torobulu Village, Laeya District 2024. Conclusion: The conclusion is that knowledge is a risk factor (OR: 5.571), exclusive breastfeeding (OR: 2.914), environmental sanitation (OR: 1.667) and income (OR: 2.513) are risk factors for stunting incidents in Torobulu Village, Laeya District.